2013
DOI: 10.1590/s0100-736x2013001100008
|View full text |Cite
|
Sign up to set email alerts
|

Abortos por Neosporacaninum em bovinos do sul de Minas Gerais

Abstract: Este estudo avaliou a participação de Neospora caninum em casos de abortos em bovinos provenientes de propriedades rurais da região sul de Minas Gerais por meio de análises histopatológicas, imuno-histoquímicas (IHQ) e pela reação em Cadeia de Polimerase (PCR). O material utilizado foi obtido de um estudo retrospectivo de casos de aborto recebidos pelo Setor de Patologia Veterinária da Universidade Federal de Lavras e de fetos necropsiados durante os anos de 2011 a 2013. De 60 fetos estudados, 30 (50%) tinham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
6
0
10
Order By: Relevance
“…Corbellini et al (2000) found 10% of the fetuses to be positive when they analyzed tissues of 30 fetuses using the immunohistochemical technique (IHC). Orlando et al (2013), after analyzing tissues of 60 fetuses through PCR and IHC, found 23.33% of the samples to be positive for the protozoan. Meanwhile, analyzing the brain, lung, liver, heart and intrathoracic fluid of 30 fetuses of dairy cattle from the State of Santa Catarina, Macedo et al (2017) found 38.8% positives through the PCR technique, 25% through immunohistochemistry and 26.7% through of the ELISA.…”
Section: Aborted Bovine Fetusmentioning
confidence: 99%
“…Corbellini et al (2000) found 10% of the fetuses to be positive when they analyzed tissues of 30 fetuses using the immunohistochemical technique (IHC). Orlando et al (2013), after analyzing tissues of 60 fetuses through PCR and IHC, found 23.33% of the samples to be positive for the protozoan. Meanwhile, analyzing the brain, lung, liver, heart and intrathoracic fluid of 30 fetuses of dairy cattle from the State of Santa Catarina, Macedo et al (2017) found 38.8% positives through the PCR technique, 25% through immunohistochemistry and 26.7% through of the ELISA.…”
Section: Aborted Bovine Fetusmentioning
confidence: 99%
“…In Brazil, N. caninum was considered an important abortifacient agent in cattle (CORBELLINI et al, 2002;SANTOS et al, 2005b;CORBELLINI et al, 2006;ORLANDO et al, 2013;PESCADOR et al, 2007;CABRAL et al, 2009). Corbellini et al (2002) showed in Rio Grande do Sul state, southern Brazil, 81% of the aborted fetuses with brain lesions suggestive of N. caninum.…”
Section: Introductionmentioning
confidence: 99%
“…Dezenove fetos, que apresentaram lesões compatíveis com infecção por N. caninum e confirmação diagnóstica por IHQ e PCR em 14 deles, foram descritos por Orlando et al (2013). Nos outros 30 fetos, sem lesões microscópicas, não podem ser descartadas causas não infecciosas de aborto, evidenciadas no histórico desses casos; em duas propriedades houve relato de medicação com corticoide nas vacas gestantes e, em várias propriedades, havia histórico de escassez alimentar.…”
Section: Discussionunclassified
“…Entre as diversas etiologias do aborto, destacam-se as de origem infecciosa, com abortos causados por protozoários, bactérias, vírus e fungos. Abortos por protozoários em bovinos são associados principalmente à infecção por Neospora caninum (Corbellini et al 2002, Orlando et al 2013, mas podem ser causados também por Tritrichomonas foetus (Alves et al 2011). Abortos bacterianos são associados a Brucela abortus, Leptospira sp., Listeria monocytogenes e Campylobacter sp.…”
Section: Introductionunclassified